Communication for business and the professions - hayes Andrews, Patricia; Baird, John E. (Dubuque,IA: Brown benchmark, 1995)
Contents: 1. communication in organizations, management theory and practice, communication fuctions, channels, and networks, 2. dyadic communication, fundamentals of communication, principles of interviewing, 3. small group communication, fuctions and sociemotional variables, 4. public communication, preparing for and supporting the public speech...
Notes p. 462-493
Keywords: Comunicación Organizacional